How women represent women political parties, gender, and representation in the state legislatures - Osborn, Tracy L. 1975- (Oxford University Press, 2012)
This title argues that political parties fundamentally structure the ways in which women legislators represent women's interests. Using original election, sponsorship and roll call data across the US state chambers, Osborn shows how parties shape the policy alternatives women offer.